Comparison of Rapid Rehabilitation after Anterior Cruciate Ligament Reconstruction with Tensioning Technique and Traditional Rehabilitation. (1st July 2022) - Jin, Tianfu; Li, Yanlin; Yang, Guiran; Liao, Xinyu; Wang, Guoliang; Wang, Fuke
Abstract : To investigate the efficacy of a fast rehabilitation program for the recovery of knee joint function after arthroscopic autologous hamstring tendon transplantation for reconstruction of the anterior cruciate ligament (ACL), from January 1, 2017, to March 31, 2019, a total of 65 patients with ACL injury were randomly divided into a study group and a control group. Both groups were treated with autologous hamstring tendon to reconstruct the anterior cruciate ligament, arthroscopic transplantation, and decompression techniques. The research group was treated with a fast rehabilitation program. The control group was treated with traditional rehabilitation program. Knee flexion angles were measured at 2, 4, and 8 weeks postoperatively. KT-1000 knee anterior stability was measured at 3, 6, and 12 months after operation. Knee function was assessed by subjective knee function assessment scale (IKDC) and Lysholm knee score. The knee curvature, KT-1000 measurement, IKDC score, and Lysholm score were compared between the two groups before and after treatment. KT-1000 measured value, IKDC score, and Lysholm score in 2 groups were significantly improved 3, 6, and 12 months compared with those before treatment, and the difference was statistically significant (P < 0.001 ). Comparison between the two groups: 2 weeks, 4 weeks, and 8 weeks after treatment, the knee curvature in the study group was better than that in the control group, and the difference was statistically significant (P < 0.001 ); there was no significant difference in the measured values of KT-1000 between the two groups 3, 6, and 12 months after treatment (P > 0.05 ); IKDC score and Lysholm score in the study group 3 and 6 months after treatment were significantly better than those in the control group, with statistical significance (P < 0.001 ); there was no significant difference in IKDC score and Lysholm score between the two groups 12 months after treatment (P >0.05). Autograft hamstring tendon transplantation and tense-reducing technique for anatomical reconstruction of anterior cruciate ligament under arthroscopy combined with rapid rehabilitation program can quickly, safely, and effectively restore the knee function of patients, greatly shortening the rehabilitation period of patients.